Економічна безпека підприємств сільського господарства в інноваційно-інвестиційній діяльності - Трусова, Наталя Вікторівна; Гривківська, О. В.; Котвицька, Н. М.; Trusova, Natalia; Hryvkivska, O. V.; Kotvytska, N. M. (Мелітополь : ТДАТУ, 2022)
UA: В статті розглянуто практичні аспекти нарощування рівня економічної безпеки підприємств сільського господарства як системи, що уособлює в собі стан стійкої рівноваги компонент їх інноваційноінвестиційної діяльності. Представлено розрахунки рівня фінансової, виробничої, кадрової, екологічної, ринкової, соціальної компонент інноваційно-інвестиційної діяльності, що забезпечують економічну безпеку підприємств сільського господарства (агрохолдингів) при взаємодії виокремленних та узгоджених індикаторів. EN: The article considers practical aspects of increasing the level of economic security of agricultural enterprises as a system that embodies the state of stable equilibrium of its components in the trajectory of innovation and investment activity when the environment changes, taking into account the restructuring of amplification factors. The necessity of a synergetic approach to balancing the state of stable equilibrium of functional components of economic security is proved. It is substantiated that economic security creates such a “security corridor” of the enterprise, which ensures its long-term progressive development, embodying it as a system that changes in response to any changes in the environment; forming a stable trajectory of innovation and investment activity; maintaining their synchronicity and rhythm by restructuring the random factors of influence, reducing bifurcation (state of unstable equilibrium), determining the critical point and increasing the amplification (action) of system parameters for further formation of new order imperatives. A methodical approach to the diagnosis of forming components of economic security of agricultural enterprises, which minimizes their number, avoids double counting of coefficients by forming a system of indicators for each component, taking into account the contour of the amplification (bifurcation) of the system equilibrium. The indicators of functional components of economic security of agricultural enterprises were combined. Diagnosis of economic security is carried out and indicators of functional components of agroholdings of Ukraine are identified. The level of economic security and its functional components is forecasted. The model of the optimal level of economic security of agricultural enterprises (agroholdings) in the interaction of isolated of components of the innovation and investment activity and their agreed indicators is presented.
Economic security of agricultural enterprises in the trajectory of innovation and investment activity
Keywords: економічна безпека; ризики економічної безпеки; підприємства; сільське господарство; агрохолдинги; інноваційно-інвестиційна діяльність; economic security; risks of economic security; enterprises; agriculture; agroholdings; innovation and investment activity